Do adapted vignettes improve medical decision‐making capacity for individuals with Alzheimer's disease? - Thalén, Liv; Heimann Mühlenbock, Katarina; Almkvist, Ove; Eriksdotter, Maria; Sundström, Erik; Tallberg, Ing‐Mari (Scandinavian journal of psychology, 2017)
Medical decision‐making capacity (MDC) is known to decline in individuals with Alzheimer's disease (AD). The vignette method uses hypothetical information as a prerequisite for measuring the capacity to make well‐informed decisions to clinical trials. Our aim was to investigate if adapted vignettes can help individuals with mild AD to assimilate information, make decisions and express them in an understandable way, compared to corresponding decisions based on linguistically more demanding vignettes, as measured by the Swedish Linguistic Instrument for Medical Decision‐making (LIMD). Two vignettes from LIMD were altered linguistically with the aim to facilitate understanding for individuals with AD. An experimental within‐subject design was used to study the influence on MDC of readability (original/adapted vignettes) and content (two different clinical trials). We included 24 patients with mild AD in this prospective study, which read all four vignettes along with a few other tests. This allowed us to investigate the association between MDC and cognitive function. Adapted vignettes did not yield significant differences regarding MDC as compared with original vignettes using a two‐way repeated measures analysis of variance. A difference was found between the two clinical trials where LIMD score was significantly higher for Kidney disease than hypertension vignettes. Our results indicate that adapted vignettes may not improve MDC for individuals with mild AD. MDC was affected by which clinical trial the vignettes regarded, which implies that other factors affecting MDC need to be investigated, like length of text and vocabulary used.